Structural mechanics a revision of Structural Mechanics - Morgan, W. (William) 1906- (Longman, 1996)
This classic text provides the theory of structures and design methods of structural members using elementary mathematics. The new edition has been brought up to date with British Standards, and the examples have also been updated.